Transcriptional profiling reveals intrinsic mRNA alterations in multipotent mesenchymal stromal cells isolated from bone marrow of newly-diagnosed type 1 diabetes patients. Issue 1 (December 2016) - de Lima, Kalil; de Oliveira, Gislane; Yaochite, Juliana; Pinheiro, Daniel; de Azevedo, Júlia; Silva Jr, Wilson; Covas, Dimas; Couri, Carlos; Simões, Belinda; Voltarelli, Julio; Oliveira, Maria; Malmegrim, Kelen
Abstract Background Bone marrow multipotent mesenchymal stromal cells (MSCs) are a diverse subset of precursors that contribute to the homeostasis of the hematopoietic niche. MSCs can be isolated and expanded in vitro and have unique immunomodulatory and regenerative properties that make them attractive for the treatment of autoimmune diseases, including type 1 diabetes (T1D). Whether autologous or allogeneic MSCs are more suitable for therapeutic purposes has not yet been established. While autologous MSCs may present abnormal function, allogeneic cells may be recognized and rejected by the host immune system. Thus, studies that investigate biological characteristics of MSCs isolated from T1D patients are essential to guide future clinical applications. Methods Bone marrow-derived MSCs from recently diagnosed type 1 diabetes patients (T1D-MSCs) were compared with those from healthy individuals (C-MSCs) for morphological and immunophenotypic characteristics and for differentiation potential. Bioinformatics approaches allowed us to match absolute and differential gene expression of several adhesion molecules, immune mediators, growth factors, and their receptors involved with hematopoietic support and immunomodulatory properties of MSCs. Finally, the differentially expressed genes were collated for functional pathway enrichment analysis. Results T1D-MSCs and C-MSCs were similar for morphology, immunophenotype, and differentiation potential. Our absolute gene expression results supported previous literature reports, while also detecting new potential molecules related to bone marrow-derived MSC functions. T1D-MSCs showed intrinsic abnormalities in mRNA expression, including the immunomodulatory molecules VCAM-1, CXCL12, HGF, and CCL2. Pathway analyses revealed activation of sympathetic nervous system and JAK STAT signaling in T1D-MSCs. Conclusions Collectively, our results indicate that MSCs isolated from T1D patients present intrinsic transcriptional alterations that may affect their therapeutic potential. However, the implications of these abnormalities in T1D development as well as in the therapeutic efficacy of autologous MSCs require further investigation.